Sinergi Akademisi Dan Umkm Kuliner Dalam Penerapan Good Manufacturing Practices Untuk Peningkatan Kualitas Dan Daya Saing Produk Di Sukabumi - Hastiningsih, Wahyu Tri; Restama, Arie; Huda, Ersyafaat (Bengawan : Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a vital role in strengthening food security and supporting the local economy. However, many small-scale food producers still struggle with the implementation of Good Manufacturing Practices (GMP), production efficiency, and consistent product quality. This community service program aimed to improve the competence of JAKATA Sukabumi MSME in managing its culinary business to be more hygienic, efficient, and competitive. The program applied a Participatory Action Research (PAR) approach that involved the partner actively in each stage—problem identification, training, implementation, and evaluation. The results indicated an increase in participants’ understanding of food safety by 38%, an average production cost reduction of 12%, and better cleanliness standards and product consistency. Furthermore, the activity encouraged a shift in mindset toward data-based management and digital marketing for business development. The program effectively facilitated knowledge transfer between academics and business owners, fostering independence and professionalism among local culinary entrepreneurs. Keywords: culinary MSMEs; Good Manufacturing Practices; Participatory Action Research; production efficiency; empowerment